2020
DOI: 10.20524/aog.2020.0566
|View full text |Cite
|
Sign up to set email alerts
|

Identifying predictors and evaluating the role of steroids in the prevention of post-embolization syndrome after transarterial chemoembolization and bland embolization

Abstract: Background Transarterial chemoembolization (TACE) and bland embolization (TAE), performed for hepatocellular carcinoma (HCC), are often complicated by post-embolization syndrome (PES). There are limited data regarding the incidence of PES after TAE and the role of steroids in PES. We report the incidence of PES post TACE and TAE, identify predictors, and evaluate the role of steroids in PES. Methods Demographic and clinical variables of patients who underwent embolizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Additionally, methylprednisolone reduced the inflammatory response and pain after other interventional radiology procedures, such as endovascular aortic repair and transarterial chemoembolization of the liver (TACE) [ 9 , 16 ]. On the other hand, two other TACE studies in 171 and 125 patients showed no effect of dexamethasone on the severity of PES symptoms [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, methylprednisolone reduced the inflammatory response and pain after other interventional radiology procedures, such as endovascular aortic repair and transarterial chemoembolization of the liver (TACE) [ 9 , 16 ]. On the other hand, two other TACE studies in 171 and 125 patients showed no effect of dexamethasone on the severity of PES symptoms [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This post-embolization syndrome (PES) presents with fever, right upper quadrant abdominal pain, and nausea with or without vomiting [ 36 ]. PES is associated with prolonged hospital stays and recurrent admissions, but it is also considered an early predictor of worse overall survival [ 36 , 37 ]. Prophylactic administration of steroids and 5-HT3 receptor antagonists has been used to prevent PES [ 38 ].…”
Section: Treatment Proceduresmentioning
confidence: 99%
“…Postembolization syndrome, a commonly described adverse event after DEB-TACE in humans that consists of nausea, fever, fatigue, and abdominal pain, 18,19 was characterized as either occurring or not occurring after NO STASIS or STASIS treatments. In our patient population, diarrhea was included as a clinical sign attributable to PES based on our experience of performing these procedures with and without chemotherapy.…”
Section: Sample Collectionmentioning
confidence: 99%